Predisposing Factors in Preventing The Transmission of Drug-Resistant TBC: A Qualitative Study in Jember - Atmawati, Siti Dwiana; Fajrin, Fifteen Aprila; Mufida, Diana Chusna (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Drug-Resistant Tuberculosis (DR TB) is a form of tuberculosis caused by Mtb bacteria resistant to anti-tuberculosis drugs (OAT). The prevalence of DR TB in Jember has significantly increased over the years, and many still refuse treatment. These individuals actively spread the bacteria to people at home or in the workplace. This research aims to identify predisposing factors in preventing the transmission of DR TB based on knowledge, attitudes, and beliefs. It is a qualitative case study involving primary subjects, DR TB patients, additional information from patient support organizations, and health department officials in Kab. Jember. The criteria for research subjects are residing in Kab. Jember, undergoing treatment, and willing to participate. The subject selection technique uses purposive sampling, resulting in 10 individuals. Data collection techniques involve in-depth interviews and observations. Data presentation follows the guidelines of Milles and Huberman, employing Thematic Content Analysis (TCA) for analysis. Data validity checks use credibility and dependability tests with source and technique triangulation. The research results indicate varying knowledge among subjects regarding DR TB prevention, with most obtaining information from healthcare professionals and patient support. In terms of attitude perspectives, all subjects show a positive response, expressing willingness to prevent DR TB transmission. Belief perspectives reveal diverse actions in DR TB transmission prevention. Most trust advice from healthcare professionals and patient support, while a minority still believe in herbal treatments and the culture of "tirah" to support TB treatment. In conclusion, knowledge, attitude, and belief perspectives are positive, but there is room for improvement in the behavior of implementing DR TB transmission prevention measures.